Основні чинники професійного самовизначення старшокласників - Єлова, Тетяна; Elova, Tatiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті визначено та проведено аналіз чинників професійного самовизначення учнів старших класів у сучасних умовах. Наведено аналіз основних класифікацій таких чинників, що мають місце у науковій літературі. The paper identifies and analyzes the factors of vocational self – determination of senior pupils in the modern world. An analysis of the major cllassifications of the factors that are presented in the scientific literature has been done. The basic psychological aspects of professional self-determination have been examined; the concept and content of professional self-determination have been exposed with their major components. The peculiarities of professional plan have been outlined and is influence on the process of secondary school leavers’ self-determination. The results of the investigation of the process of school leavers’ professional self-determination have been provided, professional intentions, interests, needs have been ascertained, factors that influence professional choice have been analyzed.
Key factors in vocational self-determination of senior pupils
Keywords: професійне самовизначення; чинники професійного самовизначення; vocational self-determination; factors of vocational self-determination